2015
DOI: 10.1038/srep16683
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 drives the pathogenesis of acquired cholesteatoma by promoting local inflammation and bone destruction

Abstract: Acquired cholesteatoma is a chronic inflammatory disease characterized by both hyperkeratinized squamous epithelial overgrowth and bone destruction. Toll-like receptor (TLR) activation and subsequent inflammatory cytokine production are closely associated with inflammatory bone disease. However, the expression and function of TLRs in cholesteatoma remain unclear.We observed inflammatory cell infiltration of the matrix and prematrix of human acquired cholesteatoma, as well as dramatically increased expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…Importantly, TLR4-deficiency in mice was already shown to be protective against cholesteatoma-driven hearing loss and bone destruction by reduction of local expression of pro-inflammatory cytokines and osteoclast formation [14]. In summary, we demonstrated that stem cells residing in cholesteatoma are the cellular mediators of its highly pro-inflammatory environment, suggesting a distinct role of ME-CSCs as drivers in cholesteatoma progression.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Importantly, TLR4-deficiency in mice was already shown to be protective against cholesteatoma-driven hearing loss and bone destruction by reduction of local expression of pro-inflammatory cytokines and osteoclast formation [14]. In summary, we demonstrated that stem cells residing in cholesteatoma are the cellular mediators of its highly pro-inflammatory environment, suggesting a distinct role of ME-CSCs as drivers in cholesteatoma progression.…”
Section: Discussionmentioning
confidence: 52%
“…In 2015, Si and colleagues extended these findings by demonstrating TLR4 as a major driver of cholesteatoma pathogenesis in terms of promoting both inflammation and bone destruction. Expression of TLR4 was particularly shown to be correlated with disease severity in terms of increased invasion, bone destruction, and hearing loss [14]. Although an up-regulation of TLR2 was observable in cholesteatoma tissue [13], deficiency in TLR2 in mice did not affect disease severity or inflammatory responses [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the perimatrix of acquired cholesteatoma, there is inflammatory cell infiltration such as lymphocyte and polymorphonuclear cells. [12][13][14] Acute inflammation is triggered by events such as bacterial or viral infections, trauma, tissue necrosis, and immune reactions. T lymphocytes play a greater role in the response of the body to viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…There is not seldom a concomitant infection of the medial part of the ear canal, which leads to a faster expansion of the disease, and the only treatment is surgery [4]. Interesting findings by Si et al [19] and Jiang et al [26] show a relationship between high expression of TLR4 in cholesteatoma matrix, and local bone destruction and inflammatory response.…”
Section: Introductionmentioning
confidence: 99%